Managing innovation and entrepreneurship - Hisrich, Robert D.; Kearney, Claudine (SAGE Publications, Inc., 2014)
The first book to look at innovation/entrepreneurship from an international perspective, this new text provides a step-by-step process for managing innovation and entrepreneurship in an organization in both turbulent and stable economic times. Authors